2023
DOI: 10.1126/sciadv.ade0869
|View full text |Cite
|
Sign up to set email alerts
|

Identification of AXL as a co-receptor for human parvovirus B19 infection of human erythroid progenitors

Abstract: Parvovirus B19 (B19V) infects human erythroid progenitor cells (EPCs) and causes several hematological disorders and fetal hydrops. Amino acid (aa) 5–68 of minor capsid protein VP1 (VP1u 5–68aa ) is the minimal receptor binding domain for B19V to enter EPCs. Here, we carried out a genome-wide CRISPR-Cas9 guide RNA screen and identified tyrosine protein kinase receptor UFO (AXL) as a proteinaceous receptor for B19V infection of EPCs. AXL gene silencing in ex vivo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 67 publications
0
11
0
Order By: Relevance
“…In line with this strategy, we found that the VP1u of B19V harbors an RBD, which interacts with an erythroid-specific surface molecule(s) required for virus internalization in the permissive EPCs [12,14,15]. Recently, the tyrosine protein kinase receptor UFO (AXL) was found to interact with the VP1u and to be required for virus uptake [45]. In the airway, AXL is expressed exclusively in the basal cells, which are progenitors of all cells in the respiratory epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this strategy, we found that the VP1u of B19V harbors an RBD, which interacts with an erythroid-specific surface molecule(s) required for virus internalization in the permissive EPCs [12,14,15]. Recently, the tyrosine protein kinase receptor UFO (AXL) was found to interact with the VP1u and to be required for virus uptake [45]. In the airway, AXL is expressed exclusively in the basal cells, which are progenitors of all cells in the respiratory epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this strategy, we found that the VP1u of B19V harbors an RBD, which interacts with an erythroid-specific surface molecule(s) required for virus internalization in the permissive EPCs [ 12 , 14 , 15 ]. Recently, the tyrosine protein kinase receptor UFO (AXL) was found to interact with the VP1u and to be required for virus uptake [ 16 ]. In the airway, AXL is expressed exclusively in the basal cells, which are progenitors of all cells in the respiratory epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…The RBD structure adopts a spatial configuration of three alpha helices [ 13 ], and binds a receptor whose expression is restricted to erythroid cells [ 14 ], coinciding with the homing of BFU-E cells to the erythroblastic islands in the bone marrow and subsequent differentiation to CFU-E, proerythroblasts, and early basophilic erythroblasts [ 15 ]. The tyrosine protein kinase receptor UFO (AXL) was found to interact specifically with the RBD, and to contribute to virus uptake [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The cultures/cells were then incubated in a humidified incubator with 5% CO 2 at 37°C for 2 hours before being washed with D-PBS three times. We carried out vector internalization assay using a previously published method (50). Cells were washed with Accutase (#AT104, Innovative Cell Technologies, Inc.) three times and then incubated with Accutase at 37°C for 1 hour.…”
Section: Methodsmentioning
confidence: 99%